Ministry of Trade and Industry Decree No. 1351 of the year 2016 = وزارة التجارة والصناعة قرار رقم 1351 لسنة 2016 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic